2019
DOI: 10.1002/ejoc.201900776
|View full text |Cite
|
Sign up to set email alerts
|

DBN‐Catalyzed Regioselective Acylation of Carbohydrates and Diols in Ethyl Acetate

Abstract: The 1,5‐diazabicyclo[4.3.0]non‐5‐ene (DBN)‐catalyzed regioselective acylation of carbohydrates and diols in ethyl acetate has been developed. The hydroxyl groups can be selectively acylated by the corresponding anhydride in EtOAc in the presence of a catalytic amount (as low as 0.1 equiv.) of DBN at room temperature to 40 °C. This method avoids metal catalysts and toxic solvents, which makes it comparatively green and mild, and it uses less organic base compared with other selective acylation methods. Mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…In kinetic resolution experiments and other 1 : 1 competition experiments it is common practice to select a single conversion point for the determination of relative reaction rates, often at conversions of around 50 %. [ 5d , 16 , 17 , 24 ] However, in order to limit the influence of the second acylation step on the ratio of the mono‐acylation, the 30 % conversion point seems more appropriate. From these measurements we derived the relative rate constant k rel,a30% defined as the ratio between the concentrations of monoesters 2b(a – g) and 3b(a – g) (Figure 2 b, for more details see Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…In kinetic resolution experiments and other 1 : 1 competition experiments it is common practice to select a single conversion point for the determination of relative reaction rates, often at conversions of around 50 %. [ 5d , 16 , 17 , 24 ] However, in order to limit the influence of the second acylation step on the ratio of the mono‐acylation, the 30 % conversion point seems more appropriate. From these measurements we derived the relative rate constant k rel,a30% defined as the ratio between the concentrations of monoesters 2b(a – g) and 3b(a – g) (Figure 2 b, for more details see Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…For substrates with an equatorial substitution at the γ-positions of the reacting hydroxy group (see the labels in 118), Ru-(PPh 3 ) 3 Cl 2 usually gave a better yield. For instance, nonprotected methyl β-D-galactopyranoside (118) was converted to the 3-O-epimerized product (148, D-gulose derivative) in 72% yield.…”
Section: Oxidation By Metal Catalystsmentioning
confidence: 99%
“…117 Ren, Tang, and coworkers reported that 1,5-diazabicyclo[4,3,0]non-5-ene (DBN) can catalyze regioselective acylation of carbohydrates in a similar mechanism involving bivalent hydrogen bonding between the catalyst and diols. 118 Schmidt, Peng, and co-workers focused on the cyanide ion. Cyanide ion is more basic than acetate ion, and thus, it would further increase the rate of acylation reactions (Figure 23a).…”
Section: Anion Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The regioselectivity can for instance be determined by a preference for cis-vicinal diols [16,[32][33][34] , a preference for diequatorial vicinal diols, [25] the axial oxy effect [30] the cyanide effect [13,29] , or dual hydrogen bonding. [35,36] Another aspect of the current methods is the necessity for more steps, complexations, and long reaction times at low temperatures in order to obtain acceptable selectivities. Some of the above-mentioned approaches are illustrated in Scheme 1.…”
Section: Product Regioselectivity Dependents Solely On Relative React...mentioning
confidence: 99%